On the suitability of the conventional injection moulding process for micro featured parts replication - a doe approach - Zhiltsova, Tatiana (2009)
Injection moulding has proven to be a technology of utmost importance for micro manufacturing because of its highly process automation and low cost. This study investigates the influence of three processing parameters on the replication quality of micro features with high aspect ratio. The filling performance of pin shaped micro features attached to a thin rectangular plate was studied via design of experiments (DOE) approach, considering as input factors: the barrel temperature, mould temperature and injection speed. The polymer chosen for the experiments was polypropylene (PP) and the mould temperature was kept within the conventional range. Furthermore, the results were analysed and compared with the ones obtained via numerical simulation. The latter were obtained by modelling the experimental conditions and performing a 3D analysis, based on the Navier Stokes flow model. The experimental results reveal that the injection speed was the most significant factor affecting the replication of the micro features. In addition, quantitative information extracted from the numerical simulation results was in agreement with the tendency observed experimentally. However, it was found out that the flow lengths of the micro features were under predicted by the numerical simulation, a fact that has been referred in the literature and that may be related to the lack of rheological data to describe the polymer flow in micro channels.